2017
DOI: 10.3945/jn.116.241216
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Vitamin D Insufficiency Early in Pregnancy Is Associated with Increased Risk of Preterm Birth in Ethnic Minority Women in Canada

Abstract: Maternal vitamin D insufficiency (plasma 25-hydroxyvitamin D [25(OH)D] <75 nmol/L) may play a role in ethnic disparities in rates of preterm and spontaneous preterm births. We explored the relation between maternal plasma 25(OH)D concentration in the first trimester (8-14 wk of gestation) and the risk of preterm and spontaneous preterm births (<37 wk of gestation) by ethnicity. We designed a case-control study that included 120 cases of preterm birth (<37 wk of gestation) and 360 term controls (≥37 wk of gesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 34 publications
1
26
0
1
Order By: Relevance
“…A total of 1639 were excluded after reading titles and/or abstracts, and 75 articles were subjected to a full-text review. After reading the full text, a total of 24 cohorts were invited to participate, which included 13 cohort studies [27][28][29][30][31][32][33][34][35][36][37][38][39], seven case-control studies [40][41][42][43][44][45][46] and four cross-sectional studies [47][48][49][50].…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 1639 were excluded after reading titles and/or abstracts, and 75 articles were subjected to a full-text review. After reading the full text, a total of 24 cohorts were invited to participate, which included 13 cohort studies [27][28][29][30][31][32][33][34][35][36][37][38][39], seven case-control studies [40][41][42][43][44][45][46] and four cross-sectional studies [47][48][49][50].…”
Section: Search Resultsmentioning
confidence: 99%
“…Because three studies [29][30][31] of 24 measured serum 25(OH)D concentrations at two or three periods of pregnancies, our meta-analysis included nine studies [28][29][30][31]36,39,41,44,46] in the first trimester, 11 studies [27,[30][31][32][33][34][35]37,38,40,43] in the second trimester, and nine studies [29][30][31]42,45,[47][48][49][50] in the third trimester.…”
Section: Search Resultsmentioning
confidence: 99%
“…In a cohort study by Wagner et al, Hispanic women with serum 25(OH)D > 40 ng/ml had 79% reduced risk of preterm birth in comparison with those with serum 25(OH)D ≤ 20 ng/ml, while the reduced risk was 45% among black women [83]. Also, an increased risk of preterm birth associated with Vitamin D insufficiency in ethnic minority women in Canada [84] suggests the stratification of women based on their ethnicity in further studies. Another important thing should be considered in study design is the association of vitamin D status in different gestational age with pregnancy outcome.…”
Section: Preterm Deliverymentioning
confidence: 99%
“…Research has shown that serum 25(OH)D concentration increases by 1 ng/mL for every 100 units of vitamin D intake per day . Therefore, vitamin D supplementation of 1000 units daily in a severely vitamin D‐deficient pregnant woman with a 25(OH)D concentration of 8 ng/mL would only increase serum 25(OH)D concentration to 18 ng/mL, which is still considered deficient and well below the point at which conversion of 25(OH)D to 1,25(OH) 2 D is optimized .…”
Section: Vitamin D Preterm Birth and Preeclampsiamentioning
confidence: 99%
“…The 4 studies that have been published and not included in the most recent meta‐analysis found a significant association between maternal vitamin D deficiency and preterm birth risk. For example, in the study by Rostami et al, pregnant Iranian women enrolled at less than 14 weeks’ gestation received vitamin D supplementation based on their baseline 25(OH)D .…”
Section: Vitamin D Preterm Birth and Preeclampsiamentioning
confidence: 99%